Intervention strategies for Parkinson’s disease: the role of exercise and mitochondria - Ganggang Xu; Chunlian Ma; Chunlian Ma; Yi Yang; Yi Yang (Frontiers in Aging Neuroscience)
Parkinson’s disease (PD), a progressive neurodegenerative disorder with complex pathogenic mechanisms, exhibiting rising prevalence alongside global population aging. Its pathological hallmarks include substantial loss of dopaminergic neurons in the substantia nigra pars compacta, leading to motor symptoms (e.g., bradykinesia, rigidity) and non-motor manifestations (e.g., cognitive impairment, sleep disorders). Accumulating evidence underscores mitochondrial dysfunction—encompassing reactive oxygen species (ROS) overproduction, defective mitophagy, and impaired biogenesis—as an important contributor to PD pathogenesis. Exercise, endorsed by leading medical and sports authorities as a non-pharmacological therapeutic strategy. While mitochondrial dysfunction impairs cellular energetics in PD patients, exercise can re-establish mitochondrial homeostasis through multiple pathways: stimulating neuroprotective exerkines, regulating mitochondrial ROS balance, modulating mitochondrial biogenesis and mitophagy, and enhancing brain-derived neurotrophic factor production. Many studies demonstrate that aerobic, resistance, and mind-body exercises demonstrably improve gait stability, postural control, and cognitive function in PD patients. However, standardized exercise prescriptions for PD prevention and treatment remain underutilized in clinical practice. This review synthesizes mitochondrial pathophysiology in PD progression, exercise-mediated regulatory mechanisms, and evidence-based exercise protocols, proposing accessible exercise regimens to support PD management. By integrating molecular insights with practical strategies, this work provides foundational evidence for utilizing exercise as a non-medical intervention against PD.